BIMBINGAN TEKNIS TENAGA KERJA KONSTRUKSI UNTUK PENGAWASAN BANGUNAN GEDUNG DAN MANDOR KONSTRUKSI - Fuad Hasan Ohorella; Sammy G. M. Amahekae; Syafrudin I. Latuconsina; Imran Oppier (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The building is one of the human needs and is used as a place to live and do other activities, it consists of a combination of several materials and constructions to function as planned. Construction is part or all of the activities that include building construction, demolition, operation, and maintenance. One of the most essential processes in construction work is the issue of supervising construction work. As a unit in construction work, the supervisory position has two functions: monitoring and managerial. The training methods implemented in this activity are lecture, presentation, assignment, and discussion methods. Based on this, the Ministry of Public Works and Public Housing, Director General of Construction Development for Region VII Jayapura, collaborated with the Southeast Maluku Regency PUPR Service and Civil Engineering Study Program to carry out Bimtek activities with 32 participants. What was achieved in this activity by the participants was an increase in the knowledge and skills of supervision and construction work processes where the presenters found a significant increase in the participants when compared to the initial meeting